PENGEMBANGAN MEDIA PEMBELAJARAN INTRAKTIF PADA MATA PELAJARAN MATEMATIKA MATERI PECAHAN DI KELAS IV - Muhammad Subhan; Suci Rahma Putri; Elvi Maryanis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Development of interactive in learning mathematics fraction material in grade IV". Dharmasraya. Thesis, Dharmasraya: Elementary School Teacher Education Study Program. Faculty of Teacher Training and Education. Dharmas University Indonesia. The purpose of this study is to develop interactive learning media using games, especially in learning mathematics, to add to existing learning media in schools and produce interactive learning media development in grade IV elementary schools that are valid, practical, and effective so as to increase students' interest in learning at SDN 10 koto new.The model used in the ADDIE development includes the analysis phase, namely needs analysis, analysis of student characteristics, curriculum analysis. the design stage (design) includes the design of learning media, namely the design of research instruments, design of manufacture. The development stage is the development stage where the validity test is carried out by experts. The implementation stage is the practicality trial stage and the evaluation stage is the effectiveness test carried out at SDN 10 Koto Baru.The results of the validation assessment of interactive learning media for mathematics fraction material in the validity test by three people get an average score of 83% included in the valid category, meaning that interactive learning media in learning mathematics fraction material is in accordance with the content, and media, practicality test with a score an average of 86% is categorized as very practical, meaning that interactive learning media can be used easily in the learning process, while the effectiveness of interactive learning media with an average score of 88% is categorized as very effective, meaning that interactive learning media can increase students' learning interest .